2018
DOI: 10.1155/2018/1037083
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Angular Velocity of a Propeller with Video Camera Using Electronic Rolling Shutter

Abstract: Noncontact measurement for rotational motion has advantages over the traditional method which measures rotational motion by means of installing some devices on the object, such as a rotary encoder. Cameras can be employed as remote monitoring or inspecting sensors to measure the angular velocity of a propeller because of their commonplace availability, simplicity, and potentially low cost. A defect of the measurement with cameras is to process the massive data generated by cameras. In order to reduce the colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…As demonstrated in Fig 4A, a well-known TADF material, 4,4 0 -bis(9-carbazolyl)benzophenone, was embedded in an oxygen-permeable matrix [57,58], deposited on a substrate and exposed to various ambient oxygen concentrations by reducing the ambient pressure [65][66][67][68]. As shown in panels i-v, the emission from this material was variably quenched based on the amount of oxygen present.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in Fig 4A, a well-known TADF material, 4,4 0 -bis(9-carbazolyl)benzophenone, was embedded in an oxygen-permeable matrix [57,58], deposited on a substrate and exposed to various ambient oxygen concentrations by reducing the ambient pressure [65][66][67][68]. As shown in panels i-v, the emission from this material was variably quenched based on the amount of oxygen present.…”
Section: Plos Onementioning
confidence: 99%
“…Put another way, the rolling shutter mechanism means each row of the photodiode array is sampling a different time domain than the adjacent rows before and after. This lag often manifests as banding and geometric distortion, particularly when capturing fast-moving objects or intermittently flashing LEDs [54,56,57],-generally considered a photographic disadvantage [58]. Recently, we [59,60] and others [52] have shown that these limitations can be exploited as features to perform time-delayed fluorescence measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Then, most importantly, although the laser tachometers are built as portable devices, it is difficult for the users to point to the extremely small label on the rotating target with the laser tachometer in hands especially when the object is vibrating or in long measurement distance and the accuracy in handheld mode degrades significantly according to our evaluation in Section 4.2. Vision-based approaches [8], [9], [10], [11], [12], [13], [14] require no extra hardware on the rotating targets and can further extend the working distance with zoom lens. They also show strong environmental adaptability and robustness.…”
Section: Introductionmentioning
confidence: 99%
“…They also show strong environmental adaptability and robustness. However, for vision-based approaches with CCD/CMOS [8], [10], [11], [12], [13], the range of rotational speed to be measured is limited by the frame rate, which is normally between 30-50 fps (frames per second) and the accuracy is not good enough (error rate is over 1%) for high-precision measurement. As shown on the left of Figure . 1, high-speed rotation of drone's propellers will place significant motion blur in the recorded video of normal RGB cameras and causes failure of measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Rotating machines are present in many industry areas, like machining, turbines, motors, gears, and shafts, and the rotation speed must be under control to prevent unexpected mechanical failures [ 1 ]. Measurement system for instantaneous rotational speed (IRS) can characterize faults in mechanical systems [ 2 ], such as gears [ 3 , 4 , 5 ], engines [ 6 , 7 , 8 ], shaft torsional vibrations [ 9 ], bearings [ 10 , 11 , 12 ], high rotating speed rotating propellers [ 1 ], estimate life cycle of machines, and evaluate their work conditions. Therefore, a reliable measurement system is required to control these parts’ life cycles.…”
Section: Introductionmentioning
confidence: 99%